Organizing creativity in the innovation journey (Research in the sociology of organizations ;, 2021)
This volume brings together empirical and conceptual papers that investigate the challenges of organizing creativity in the innovation journey in and across different empirical contexts. The articles in this volume extend our understanding of the contextualized social dynamics of organizing creativity in four directions. The first direction sheds light on the temporal dynamics of organizing creativity in artistic fields. The second direction compares creative processes in arts and science, thereby examining tensions and uncertainties in the creative process unfolding in two distinctive contexts of creativity. The third direction investigates identity struggles of creative agents in organizations with clashing roles, professional norms, and ambiguities in creativity assessment. The fourth and final direction unravels the communicative journey of ideas from pitching to feedback, revealing how ideas are challenged, enriched, and acquire meaning in communicative interaction. Contributing to a situated view of creative processes in innovation, Organizing Creativity in the Innovation Journey goes beyond questions of idea generation to account for the dynamics of idea development, judgement, and dissemination - processes which are at the heart of organizing for innovation.